1985
DOI: 10.1210/jcem-60-3-523
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Glucose on Growth Hormone (GH)-Releasing Hormone-Mediated GH Secretion in Man*

Abstract: The effect of glucose on GH-releasing hormone (GHRH)-mediated GH secretion was examined in six normal young men. In two paired experiments, the six men drank a 75-g glucose solution or an equal volume of water 30 min before receiving, iv, 100 micrograms of the 44-amino acid form of human pancreatic GHRH (hGHRH-44). One week later, the same men underwent an identical experimental protocol in a cross-over trial. Basal plasma GH concentrations before hGHRH-44 administration were not statistically different in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
32
0
1

Year Published

1987
1987
2005
2005

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(36 citation statements)
references
References 15 publications
3
32
0
1
Order By: Relevance
“…However, the mechanism of the suppressing effect of hyperglycemia on GH secretion in normal subjects is not clear, nor is the cause of paradoxical secretion to oral glucose in acromegaly [13][14][15]. It was reported that an acromegaly induced by an ectopic GRHproducing tumor, had a paradoxical GH secretion to oral glucose, but that an exogenous GRH load did not induce GH secretion, therefore GRH was thought not to be involved in the paradoxical GH response to oral glucose load in acromegaly [16].…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanism of the suppressing effect of hyperglycemia on GH secretion in normal subjects is not clear, nor is the cause of paradoxical secretion to oral glucose in acromegaly [13][14][15]. It was reported that an acromegaly induced by an ectopic GRHproducing tumor, had a paradoxical GH secretion to oral glucose, but that an exogenous GRH load did not induce GH secretion, therefore GRH was thought not to be involved in the paradoxical GH response to oral glucose load in acromegaly [16].…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that hyperglycemia may itself affect GH secretion. An increased plasma glucose concentration exerted an inhibitory effect on the plasma GH response to GRF in man [26]. In rats hyperglycemia has been reported not to affect the GH response to GRF [27].…”
Section: Discussionmentioning
confidence: 87%
“…Inhibition of GH response to GH-RH by high glucose was reported in healthy subjects after oral [13] or intravenous [14] administration of glucose. Thus, it is very interesting that a paradoxically high response of GH to GH-RH was observed in the H-R group even though the blood glucose concentration was much higher in the H-R group than in the L-R group.…”
Section: Discussionmentioning
confidence: 97%